The Lea affair : a British diplomat's scandal - Akena, Adoko, 1931- (New Delhi : Vikas Pub. House, 1985)
Narrative poem about Brian Alistair Lea.
Poem.
Includes bibliographical references.
Keywords: Lea, Brian Alistair -- Poetry; Uganda -- Politics and government